(untitled) (Revista Argentina de Musicología, 2009)
The etic perspective suggests the infallibility of the researcher’s judgments on his study material. The emic approach, on the other hand, indicates the need to incorporate the perspective of the insiders so as to perceive their thoughts on their music. However, who can guarantee that the translation of the insider’s perspective into the researcher’s terms is correct? What does the suitability of an emic description rely on? On pragmatics? Or on the blind trust in the informants? Moreover, what are the limits of the ethical perspective? Is this the only possible place to develop the theory? Does its suitability rest on pragmatics or on the blind trust of our own assumptions? These epistemological questions about emic/etic can be answered if the epistemological status of every perspective during the process of designing the musical research is reformulated. On the latter question the following article lies: Its aim is to develop the proposal that emic perspective works as rules to be validated, while the etic perspective makes it possible to formulate emicity hypotheses to be verified. The studycase is the way the insiders in Estancia La Candelaria (Province of Córdoba) sing. The singing shows rhythmic variations derived from the regional accent according to the performance’s particular circumstances.